2022
DOI: 10.4046/trd.2021.0179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Comorbidities in Individuals with Chronic Obstructive Pulmonary Disease: A Systematic Review

Abstract: This study aimed to describe the prevalence of comorbidities associated with chronic obstructive pulmonary disease (COPD) and their relation with relevant outcomes. A systematic review based on the PRISMA methodology was performed from January 2020 until July 2021. The MEDLINE, Lilacs, and Scielo databases were searched to identify studies related to COPD and its comorbidities. Observational studies on the prevalence of comorbidities in COPD patients and costs with health estimates, reduced quality of life, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 46 publications
(75 reference statements)
3
22
0
Order By: Relevance
“…The additional comorbidities of the patients were observed to be present in the majority of the study group, which, combined with the advanced age of the patients, supported the initial assumption of the group being considered fragile compared to the general population. In accordance with the literature, these factors effectively played a role in high COPD exacerbations in our study [17,18]. There are many studies in the literature stating that there is a negative correlation between forced expiratory volume in one second (FEV1) levels and hospital stay [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…The additional comorbidities of the patients were observed to be present in the majority of the study group, which, combined with the advanced age of the patients, supported the initial assumption of the group being considered fragile compared to the general population. In accordance with the literature, these factors effectively played a role in high COPD exacerbations in our study [17,18]. There are many studies in the literature stating that there is a negative correlation between forced expiratory volume in one second (FEV1) levels and hospital stay [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…Unlike the young population, elderly people have many comorbidities, usually take many prescription drugs, and their metabolism is slow. 39 40 …”
Section: Discussionmentioning
confidence: 99%
“…However, these results are consistent with findings of several previously reported studies analyzing the quality of life in COPD patients. According to the previous studies, poor quality of life showed an association with comorbidities, uncontrolled respiratory symptoms such as sputum, or pulmonary hyperinflation (represented by residual volume/total lung capacity), while no significant association was observed with regard to smoking history or airflow limitation [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%